2023
DOI: 10.5194/egusphere-2023-780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Overview of the Vertical Structure of the Atmospheric Boundary Layer in the Central Arctic during MOSAiC

Abstract: Abstract. Observations collected during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) provide an annual cycle of the vertical thermodynamic and kinematic structure of the atmospheric boundary layer (ABL) in the central Arctic. A self-organizing map (SOM) analysis conducted using radiosonde observations shows a range in the Arctic ABL vertical structure from very shallow and stable, with a strong surface-based virtual potential temperature (θv) inversion, to deep and near-n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Potential temperature gradients more than 5 K (100 m) -1 in nearly all of the SOM-identified patterns in Figure 2, with many greater than 15 K (100 m) -1 , and some even greater than 30 K (100 m) -1 , shows that strong stability is in fact common at this site. Potential temperature gradients in excess of 15 K (100 m) -1 , corresponding to our VSS regime (Table 2), are rarely observed outside of the interior of Antarctica, even in the Arctic (Jozef et al, 2023). Potential temperature gradients less than 1.75 K (100 m) -1 , corresponding to NN or WS regimes, occur only in patterns 6, 12, and 18 in the upper right of the SOM, emphasizing the dominance of strong stability at South Pole.…”
Section: South Polementioning
confidence: 67%
See 1 more Smart Citation
“…Potential temperature gradients more than 5 K (100 m) -1 in nearly all of the SOM-identified patterns in Figure 2, with many greater than 15 K (100 m) -1 , and some even greater than 30 K (100 m) -1 , shows that strong stability is in fact common at this site. Potential temperature gradients in excess of 15 K (100 m) -1 , corresponding to our VSS regime (Table 2), are rarely observed outside of the interior of Antarctica, even in the Arctic (Jozef et al, 2023). Potential temperature gradients less than 1.75 K (100 m) -1 , corresponding to NN or WS regimes, occur only in patterns 6, 12, and 18 in the upper right of the SOM, emphasizing the dominance of strong stability at South Pole.…”
Section: South Polementioning
confidence: 67%
“…Various thresholds to distinguish near neutral (NN), weak (WS), moderate (MS), strong (SS), very strong (VSS), and extremely strong (ESS) stability were evaluated, and the thresholds listed in Table 2 were found to best separate meaningful differences in near-surface stability across all five sites. These thresholds were also evaluated, and found to be appropriate, in a separate study based on profiles observed over Arctic sea ice as part of the MOSAiC expedition (Jozef et al 2023).…”
Section: Boundary Layer Regime Definitionsmentioning
confidence: 99%